2016
DOI: 10.1155/2016/5608198
|View full text |Cite
|
Sign up to set email alerts
|

Male Involvement in Maternal Health Planning Key to Utilization of Skilled Birth Services in Malindi Subcounty, Kenya

Abstract: Background.In Malindi, rural populations face challenges in accessing skilled birth services. Consequently, the majority of women deliver at home and only seek help when they have complications. This paper reports part findings from a study conducted to assess health priority setting process and its implication on availability, access, and use of emergency obstetric care services in Malindi.Methods. The study utilized qualitative methods to collect data from health personnel and maternal health stakeholders in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…A qualitative study in the Northern Ethiopia indicated that without the support of the husbands, GMP is unlikely to succeed [8]. It is indicated that husbands are very influential in regard to decisions for health service utilization in developing countries [18]. Other studies, though not directly related to GMP, also reported husbands as the primary spokespersons for their family, and their say and advice are also highly valued by mothers and children in utilizing health-care services [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study in the Northern Ethiopia indicated that without the support of the husbands, GMP is unlikely to succeed [8]. It is indicated that husbands are very influential in regard to decisions for health service utilization in developing countries [18]. Other studies, though not directly related to GMP, also reported husbands as the primary spokespersons for their family, and their say and advice are also highly valued by mothers and children in utilizing health-care services [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…In some parts of Ghana, men, as the heads of their families, hold the most important roles and responsibilities, and have unlimited decision-making power [13,14]. These men make important decisions, including those concerning whether their wives seek skilled care [1216]. Therefore, men’s education could play a critical role in improving maternal health in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…Spousal support and decisions concerning the use of maternal health services also influence women’s access to skilled care [11]. This could be attributed to the patriarchal system in place in Africa, in which men are usually the heads of households, with the power and authority to make decisions, including those concerning their wives’ use of maternal health services [1216], for their family members [13]. Religious factors also contribute to women’s decisions regarding ANC attendance [7].…”
Section: Introductionmentioning
confidence: 99%
“…This perception is supported by findings from SMGL's first year of implementation, which saw a 35% increase in health facility deliveries between 2012 and 2013 20 , 21 . The engagement of men and community leaders to promote behavior change for women's health is imperative in patriarchal societies, since access to care is controlled by men 29 , 30 . Interventions to change social norms should include key community members in order to achieve desired public health effects 31 – 34 .…”
Section: Discussionmentioning
confidence: 93%